2009
DOI: 10.1111/j.1741-2358.2008.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and behaviour of caregiver managers related to oral care in the community

Abstract: Results suggested that knowledge of oral care was related not only to the career but also to age and revealed a basic gap in the range of abilities between the respondent caregiver managers. Some did perform appropriate oral care and carried out the necessary processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Chiba et al. 34 revealed that lack of hope for the elderly, insufficient time for practice, lack of co‐operation of the elderly and difficulty in accessing the mouth are the main reasons given by caregivers for reluctance and inappropriate oral care. It was reported that lack of consent and co‐operation by the elderly was a common obstacle reported by caregivers 2,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Chiba et al. 34 revealed that lack of hope for the elderly, insufficient time for practice, lack of co‐operation of the elderly and difficulty in accessing the mouth are the main reasons given by caregivers for reluctance and inappropriate oral care. It was reported that lack of consent and co‐operation by the elderly was a common obstacle reported by caregivers 2,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Chiba et al [47] conducted a survey of 102 caregiver managers to investigate their knowledge, practice, and educational background regarding oral health. The data collected were also used to analyze the relationship between factors of oral health education and length of career.…”
Section: Oral Care Training For Nursing Staffmentioning
confidence: 99%
“…Knowledge within the profession will improve the environment in the oral cavity of elderly people who need intensive care. For instance, Chiba et al described that around 90% of caregiver managers recognized the importance of oral care and were interested in oral care [110]. Caregiver oral care knowledge is important for preventing AP.…”
Section: Resultsmentioning
confidence: 99%